Algorithms of follow-up in patients with head and neck cancer in relation to primary location and advancement. Consensus of Polish ENT Society Board and Head Neck Experts - Wierzbicka, Małgorzata; Markowski, Jarosław; Pietruszewska, Wioletta; Burduk, Paweł; Mikaszewski, Bogusław; Rogowski, Marek; Składowski, Krzysztof; Milecki, Piotr; Fijuth, Jacek; Jurkiewicz, Dariusz; Niemczyk, Kazimierz; Maciejczyk, Adam (Frontiers in Oncology, 2023)
The Algorithm of follow-up in head and neck cancer (HNC) patients has been prepared by a board of Polish Head Neck and Oncology Experts. The aim of this research is to focus on the specificity of HNC monitoring, to review the current trends and to adapt the Evidence Based Medicine international standards to capabilities of the local health care service. The first methodological step was to categorize HNCs according to the estimated risk of failure after the adequate first-line treatment and according to the possibility of effective salvage treatment, resulting in improved overall survival. The final method was to prepare an authors’ original monitoring algorithm for HNC groups with a high, moderate, and low risk of recurrence in combination with a high or low probability of using an effective salvage. Four categories were established: Ia. Low risk of recurrence + Effective organ preservation feasible; Ib Low risk of recurrence + Effective salvage feasible; II Moderate risk of recurrence + Effective salvage feasible; III High risk of recurrence + Effective salvage feasible; IV High risk of recurrence + No effective salvage feasible. Follow-up visit: 1. ENT examination + neck ultrasound 2. Imaging HN tests 3. Chest imaging 4. Blood tests 5. Rehabilitation (speech, swallowing) were scheduled with very different frequency, at the proposed monthly intervals, tailored to the needs of the group. The number of visits for individual groups varies from 1-8 in the first 2 years and 1-17 in the entire 5-year monitoring period. Group IV has not been included in regular follow-up having in mind that IIIrd line therapy and immune checkpoint inhibitors is available. Universal monitoring algorithm for HNC four groups with a high, moderate, and low risk of recurrence after the adequate treatment in combination with a high or low probability of using an effective salvage is an innovative approach to redeploying system resources and ensuring maximum benefit for HNC patients.